Impact of spatial distribution on the development of mutualism in microbes - Kovács, Ákos T. (Frontiers in Microbiology, 2014)
The evolution of mutualism is one of the long-standing puzzles in evolutionary biology. Why would an individual contribute to the group at the expense of its own fitness? Individual bacterial cells cooperate by secreting products that are beneficial for the community, but costly to produce. It has been shown that cooperation is critical for microbial communities, most notably in biofilms, however the degree of cooperation strongly depends on the culturing conditions. Spatial community structure provides a solution how cooperation might develop and remain stable. This perspective paper discusses recent progresses on experiments that use microbes to understand the role of spatial distribution on the stability of intraspecific cooperation from an evolutionary point of view and also highlights the effect of mutualism on spatial segregation. Recent publications in this area will be highlighted, which suggest that while mechanisms that allow assortment help to maintain cooperative traits, strong mutualism actually promotes population intermixing. Microbes provide simple and suitable systems to examine the features that define population organization and mutualism.